Perbuatan Melawan Hukum Atas Penggunaan Aplikasi Micha - Gurium, Abdul Haji; Tjoanda, Merry; Haliwela, Nancy Silvana (Pusat Kajian Hukum Bisnis Fakultas Hukum Universitas Pattimura, 2024)
The development of builders is increasing, especially in the field of information and communication technology that is growing rapidly, so that work or human needs are getting easier, with advances in technology in the form of applications that exist today. Many activities or needs can be met, such as being used to order meals through the application. However, developments in the field of technology have resulted in a michat application that is used as immoral acts which are against the law. as in Article 1365 of the Civil Code. The use of the michat application is currently used as a means of communication, but is often used to commit immoral acts. as a form of unlawful act. As a result, sanctions will be imposed. The research method that uses is normative juridical, by examining various laws and regulations and other literature related to research. The purpose is to find out and explain how the form of unlawful acts and sanctions for unlawful acts with michat application users. The results of this study show that the use of the michat application is a form of unlawful acts, moral norms and religious norms (Islam) because it is used for immoral acts and the use of the michat application is sanctioned in accordance with the law in order to get a deterrent effect for its actions and will not do similar actions. The use of the michat application is a form of unlawful action and gets sanctions according to the law. So it is necessary to give an understanding to michat application users, and there must also be government supervision of michat application users.